1970
DOI: 10.1021/ma60014a020
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Ketone Polymers. III. Energy Transfer in Ethylene-Carbon Monoxide Polymers

Abstract: Studies have been made of electronic energy transfer to and from the excited states of carbonyl groups in ethylene-carbon monoxide copolymers in decahydronaphthalene solution and in the solid phase. The results were compared with those obtained using 6-undecanone as a model ketone. The partition of photochemical reaction between singlet and triplet precursors was examined by the use l-c/s,3-cA-cyclooctadiene as a triplet quencher. About 50 % of the photochemical reaction in the carbonyl copolymer originated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…In early studies we showed by measurements of the type II process in polyethylene-carbon monoxide that the triplet reactions could be quenched by cyclooctadiene at approximately collisional rates in dilute solution, and also in the solid phase. (10,11) In this case the limiting rate is the diffusion of the cyclooctadiene through the amorphous polyethylene matrix. Studies of the quenching of type II photolysis of poly(phenyl vinyl ketone) showed that substantially all the reaction arose from the excite<l triplet state and that the quantum yields and lifetimes were dependent upon sequence distribution in phenyl vinyl ketone-styrene copolymers.…”
Section: ~D~~mentioning
confidence: 99%
“…In early studies we showed by measurements of the type II process in polyethylene-carbon monoxide that the triplet reactions could be quenched by cyclooctadiene at approximately collisional rates in dilute solution, and also in the solid phase. (10,11) In this case the limiting rate is the diffusion of the cyclooctadiene through the amorphous polyethylene matrix. Studies of the quenching of type II photolysis of poly(phenyl vinyl ketone) showed that substantially all the reaction arose from the excite<l triplet state and that the quantum yields and lifetimes were dependent upon sequence distribution in phenyl vinyl ketone-styrene copolymers.…”
Section: ~D~~mentioning
confidence: 99%
“…They reported that only oligocopolymerization of carbon monoxide (CO) with mer (molecular weight Å 350) was obtained from olefins because of several advantages offered by copolymerization of CO and norbornene after 3 the resultant copolymers. [1][2][3][4][5] First, carbon monoxdays. 7 Drent et al 9,10 was the first to use pallaide is inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…For the simplest model, if the blends contained only two phases after PCL crystallization, viz., the PCL crystalline phase and the miscible amorphous phase, the composition of the miscible amorphous phase can be calculated once the PCL degree of crystallinity is known. (2) where w copolymer and WpcL are the initial weight fraction of copolymer and PCL, respectively. Figure 4 also displays the plot of Tg vs. the composition after adjusting for the PCL crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] In a prior study, Liaw et al have successfully synthesized an alternating copolymer of CO and phenylacetylene (PA) by palladium complex. 7 Poly(PA-alt-CO) is an amorphous material with a glass transition temperature (Tg) around l00°C.…”
mentioning
confidence: 99%